Internalization of Anti-corruption Values with GEULIS SERASI: Gerakan Menulis Semangat Rantas Korupsi in MAN 5 Garut - Hadi Saputri, Santi (Yayasan Indonesia Bermutu, 2025)
Anti-corruption values ​​are one of the pillars supporting student character education. This study was conducted to describe the implementation of the GEULIS SERASI program at MAN 5 Garut in internalizing anti-corruption values. The research method used is descriptive qualitative with a phenomenological design. The data collection process was carried out through interviews, observations, and surveys. The GEULIS SERASI program or Gerakan Menulis Semangat Rantas Korupsi elaborates between anti-corruption education and writing skills training. Students who participate in this program are given an understanding of anti-corruption values ​​and are trained to produce writing through an honest process. Based on the survey conducted, it is known that the GEULIS SERASI program is able to foster students' understanding to write with full integrity, free from plagiarism practices. Students are able to understand the values ​​of anti-corruption and how to apply them in the writing process. Ultimately, this good practice becomes capital to strengthen the anti-corruption character in students not only in writing, but also in various other activities.